The architectural sources for the Museum Building - Tierney, Andrew (Four Courts Press, 2019)
If the purpose of this research project, as stated by Christine Casey at the start of this book, is to highlight the process of making (rather than meaning), then we must query the ‘making’ that went into the design itself. For the Museum Building is not just a rich combination of materials, but also a rich combination of architectural features from disparate sources. Appropriately for a scientific building, its architecture emerges from the Victorian need to travel, label, catalogue, compare, master, and ultimately distil. While Ruskin’s influence has long been acknowledged in this process, the building’s eclecticism and quality of execution have deeper roots and a longer gestation than a dependence on Ruskin alone will allow. Ruskin’s illustrations of Venice, published largely in the three volumes of The stones of Venice between 1851 and 1853, focus almost exclusively on architectural details, hardly equipment enough for so assured a change in direction. Edward McParland’s 1976 Country Life article on Trinity College and subsequent research by Douglas Scott Richardson, Eve Blau and Frederick O’Dwyer have already uncovered wider influences on Deane and Woodward, including Charles Barry’s Travellers’ Club, engravings of Venetian palazzi published in The Builder, and the mosque at Córdoba. As these studies have established, the Museum Building set Deane, Son and Woodward on a new trajectory, which would produce an extraordinary series of public and private works across two countries. The purpose of this paper is to continue the search for the stylistic ingredients in the remarkable first step on that journey.
The Museum Building of Trinity College Dublin: a model of Victorian Craftsmanship.
Keywords: Creative Arts Practice; Making Ireland; British History; English and European architecture, 18th and 19th centuries; Irish History; Irish architectural history; Victorian Ireland; Victorian studies; architectural history; Culture; History